Optical Properties of Iron Oxide Thin Films Prepared by Pulsed Laser Ablation Method - Rasha Hamid Ahmed (Tikrit Journal of Pure Science)
Iron oxide nanoparticles (Fe2O3) were prepared by pulsed Nd-YAG laser ablation technology for a target of iron oxide in ultra-pure water with a constant number of pulses (250) with different ablation energies (400, 500, 600, 700 and 800) mJ and formed a colloidal solution for each energy. Optical properties were calculated and changing the energy value on the preparation of iron nanoparticles was shown, and the value of energy gap varies from (2.88-3.04) eV according to the change in the ablation energy.